PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK MY CARAMEL 1994 (Studi Pada My Caramel 1994 Cabang Jl. Ir. Juanda) - Thesia Saskia Putri; Arwin Sanjaya (Jurnal Cakrawala Ilmiah, 2023)
The purpose of this study was to find out how the influence of the marketing mix on purchasing decisions for My Caramel 1994 products. The type of research used is a quantitative approach. The sample used consisted of 100 respondents who were customers of My Caramel 1994 Juanda City of Samarinda. Sampling was based on certain criteria or assessments and then used random sampling, namely a random sampling technique. The data analysis used was compiling data obtained from interviews, field notes, documents, and organizing the data into categories and then the data was processed and analyzed using the SPSS 26 application. The results showed that 1) the product variable had no significant effect on the purchase decision 2) the price variable had a significant effect on the purchase decision 3) the location variable had a significant effect on the decision 4) the promotion variable had a significant effect on the purchase decision 5) the product, price, location, promotion variable simultaneously significant effect on purchasing decisions. The suggestion is that product quality must be further improved by making SOP (Standard Operational Procedure) because of the four independent variables, only product variables do not affect consumer purchasing decisions. In addition, price, location, and promotions, although they affect purchasing decisions, must still be maintained.